2014
DOI: 10.4236/me.2014.55045
|View full text |Cite
|
Sign up to set email alerts
|

An Essay on Intra-Industry Trade in Intermediate Goods

Abstract: This paper contributes to the debate on the effects of international fragmentation on two-way trade in several ways. Firstly, it is the first study on determinants of horizontal and vertical intraindustry trade in intermediate goods with regard to Italy. Secondly, it studies if and how country-specific factors affect intra-industry trade in intermediate goods when heterogeneity among sectors is allowed. The topic is very important for its policy implications. As is known, the early literature distinguishing ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
3
0
1
Order By: Relevance
“…He found that differences in the country size and income were positively related to IIT as are FDI, while the distance and IIT showed a negative relationship. Pittiglio (2014) analysed intra-industry trade of intermediate goods in Italy and concluded that differences in the factor endowments and the R&D as well as the regional trade agreements enhanced VIIT, while the distance and VIIT was negatively related. Jámbor (2014) and Fertő and Jámbor (2015) analysed the country specific determinants of IIT for agri-food products for the NMS and found that the factor endowments are ambiguously related to the agri-food horizontal and vertical intra-industry trade.…”
Section: Empirical Evidencementioning
confidence: 99%
“…He found that differences in the country size and income were positively related to IIT as are FDI, while the distance and IIT showed a negative relationship. Pittiglio (2014) analysed intra-industry trade of intermediate goods in Italy and concluded that differences in the factor endowments and the R&D as well as the regional trade agreements enhanced VIIT, while the distance and VIIT was negatively related. Jámbor (2014) and Fertő and Jámbor (2015) analysed the country specific determinants of IIT for agri-food products for the NMS and found that the factor endowments are ambiguously related to the agri-food horizontal and vertical intra-industry trade.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Halbuki, küresel değer zincirleri gerçekte hem endüstri içi hem de endüstriler arası ticareti kapsamakta (OECD ve CEFTA, 2013) ve KDZ'ler ile endüstri-içi ticaret ürün farklılaşmasından çok, üretimin parçalanması sonucunda artan ara mal ticaretinden kaynaklanmaktadır. Bu sebeple, ara malların endüstri içi ticaretini nihai malların endüstri içi ticaretinden ayrı değerlendirilmek önemlidir (Pittiglio, 2014).…”
Section: Kdz'ler İle şEki̇llenen "İkti̇sadi̇ Bağimsizlik" Ve Gelene...unclassified
“…Unfortunately, CI research continues to insist that consumers rate hypothetical products and services based on country associations despite the inadequate and incomplete origin information. The prominence of global sourcing in manufacturing supply chains leading to the rise of trade in intermediate goods (Ali and Dadush, 2011; Pittiglio, 2014), usually as components, further obscures CI information from consumers and requires B2B buyers to be the source of reliable origin information. Such a persistent departure from reality enabled researchers to criticize existing CI research for being overly dependent on consumer samples and unrealistic purchasing scenarios.…”
Section: Literature Reviewmentioning
confidence: 99%